Design of acid‐activated cell‐penetrating peptides with nuclear localization capacity for anticancer drug delivery. (7th June 2021) - Huang, Sujie; Zhu, Zhongwen; Jia, Bo; Zhang, Wei; Song, Jingjing
Abstract : Camptothecin (CPT), a DNA‐toxin drug, exerts anticancer activity by inhibiting topoisomerase I. Targeted delivery of CPT into the cancer cell nucleus is important for enhancing its therapeutic efficiency. In this study, a new type of acid‐activated cell‐penetrating peptide (CPP) with nuclear localization capacity was constructed by conjugating six histidine residues and a hydrophobic peptide sequence, PFVYLI, to the nuclear localization sequence (NLS). Our results indicated that HNLS‐3 displayed significant pH‐dependent cellular uptake efficiency, endosomal escape ability, and nuclear localization activity. More importantly, the HNLS‐3–CPT conjugate showed obviously enhanced cytotoxicity and selectivity compared with CPT. Taken together, our findings provide an effective approach to develop efficient CPPs with both cancer‐ and nucleus‐targeting properties. Abstract : Cell‐penetrating peptide HNLS‐3 displayed significant pH‐dependent cellular uptake efficiency, endosomal escape ability and nuclear localization activity.